Prisoners of Our Thoughts : Viktor Frankl's Principles for Discovering Meaning in Life and Work. - Pattakos, Alex (Berrett-Koehler Publishers, 2017)
7 Principles for Finding Meaning in Life & Work World-renowned psychiatrist Viktor Frankl's Man's Search for Meaning is one of the most important books of modern times. Frankl's extraordinary personal story of finding meaning amid the horrors of the Nazi concentration camps has inspired millions. Frankl vividly showed that you always have the ultimate freedom to choose your attitude--you don't have to be a prisoner of your thoughts. Dr. Alex Pattakos--who was urged by Frankl to write Prisoners of Our Thoughts--and Elaine Dundon, a personal and organizational innovation thought leader, show how Frankl's wisdom can help readers find meaning in every moment of their lives. Drawing on the entire body of Frankl's work, they identify seven "core principles" and demonstrate how they can be applied to everyday life and work. This revised and expanded third edition features new stories, practical exercises, applications, and insights from the authors' new work in MEANINGology®. Three new chapters outline how we all can benefit by putting meaning at the core of our lives, work, and society. And a new chapter on Viktor Frankl's legacy illustrates how his work continues to influence so many around the world.